Flipped classroom in higher health education: a systematic review (Research, Society and Development, 2021)
This study aims to identify the contributions of the inverted classroom in the teaching-learning process of health care teachers and students. This is a systematic review. The guiding question was "What are the contributions of the inverted classroom in health education?" then, a search was carried out in four electronic databases: the Latin American and Caribbean Literature on Health Sciences (LILACS), the Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), the Nursing Database (BDENF), and the Scientific Electronic Library Online (SciElo). 77 studies were included. Most publications were related to the undergraduate level of education (n=57) followed by postgraduate education (specialization, residency, master's and doctorate) (n=20). With the use of an inverted room in the context of the medical area (n=55), dentistry (n=11), nursing (n=8), physiotherapy (n=1), pharmacy (n=2). The main contributions to higher education in health were the increase in learning outcomes and the ability to understand the subjects, prior preparation for classroom classes, the variability of technological and material resources, the possibility of carrying out interactive teaching activities. It was identified in the study that the use of the inverted classroom promotes autonomy, self-directed study and skills development through blended learning. Training aimed at teachers is necessary in order to encourage them to use the inverted classroom teaching and learning strategy.